2017
DOI: 10.5216/rpt.v46i2.47572
|View full text |Cite
|
Sign up to set email alerts
|

Head Lice in School Children in Uberlandia, Minas Gerais State, Brazil

Abstract: School-aged children have shown to be the group most susceptible to Pediculus capitis infestation, possibly due to their habits and behaviors. The purpose of the study was to verify the prevalence of head pediculosis in preschool children from Uberlândia, MG, and factors associated with infestation. The children's parents or guardians were also evaluated regarding socioeconomic status, knowledge of symptomatology and control of this ectoparasitosis. Data were obtained by direct examination of each child's head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The prevalence of overall infestation in girls observed at the present study is similar to the reported ones in other studies from Brazil and other countries 9,17,31 . The differences between sex may be associated to behavioral variations 6 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The prevalence of overall infestation in girls observed at the present study is similar to the reported ones in other studies from Brazil and other countries 9,17,31 . The differences between sex may be associated to behavioral variations 6 .…”
Section: Discussionsupporting
confidence: 91%
“…Considering that the empty nit can remain attached to the hair as long as six months after the infestation 4 , the finding of an empty nit could result in a false positive for head lice infestation, mainly in children with long hair 10,19,25 . Considering that, this difference may be more related to hair length than to sex ratio 6,9 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Infestation with this ectoparasite is often asymptomatic and not pathogenic for humans, but it causes skin irritation and sometimes leads to skin infection due to skin itching (1,2). But the importance of this pollution is its widespread prevalence, so that in recent decades, most of the countries of the world in North America, South America, Australia, Europe, and Asia have been involved in this pollution, and its prevalence is increasing (3)(4)(5)(6). As a result, controlling and preventing the spread of this Infestation is very important.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%